2021
DOI: 10.18860/neu.v14i1.12753
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clay Materials Used for Pottery Purposes From Rendeng, Malo, Bojonegoro

Abstract: Clay material from Rendeng, Malo, Bojonegoro was studied by mineralogy and physicochemical characterization to evaluate its potential suitability as a raw material in pottery application. X-ray Diffraction (XRD) and Fourier Transform-Infrared (FTIR) spectrometry were used to establish the mineralogy composition. Meanwhile the physical properties were identified by particle size distribution and consistency limits. Chemical composition was carried out by X-ray Fluorescence Spectrometer (XRF).  The results of XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The main component of natural clay from Gowa, South Sulawesi are Fe2O3, Al2O3, and SiO2, while the main mineral components are quartz, kaolinite, and hematite (Side & Putri, 2022). XRD result of natural clay from Bojonegoro, East Java showed that it consists of kaolin, quartz, and feldspar minerals (Setyaningrum et al, 2021). While the main mineral components of natural clay in Gema village, Kampar, Riau Province consists of quartz, montmorillonite, and kaolinite (Yanti & Muhktar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The main component of natural clay from Gowa, South Sulawesi are Fe2O3, Al2O3, and SiO2, while the main mineral components are quartz, kaolinite, and hematite (Side & Putri, 2022). XRD result of natural clay from Bojonegoro, East Java showed that it consists of kaolin, quartz, and feldspar minerals (Setyaningrum et al, 2021). While the main mineral components of natural clay in Gema village, Kampar, Riau Province consists of quartz, montmorillonite, and kaolinite (Yanti & Muhktar, 2015).…”
Section: Introductionmentioning
confidence: 99%